Extracting foraging behavior from passive acoustic monitoring data to better understand harbor porpoise (Phocoena phocoena) foraging habitat use. Issue 4 (21st June 2022) - Todd, Nicole R. E.; Jessopp, Mark; Rogan, Emer; Kavanagh, Ailbhe S.
Abstract: For odontocetes, passive acoustic monitoring (PAM) can be used to differentiate between occurrence and foraging through analysis of click characteristics. Feeding buzzes and navigation/searching echolocation clicks of harbor porpoise ( Phocoena phocoena ) were differentiated within C‐POD data from northwest Ireland between 2009 and 2017. The spatiotemporal distribution of foraging behavior was investigated using generalized additive modelling, at multiple temporal scales. Both the presence/absence of buzzes and foraging intensity (defined by buzz:click ratios) were determined. Feeding buzzes were identified in one third of porpoise positive hours, ranging from 15% in summer, to 40% in autumn, highlighting seasonal variation irrespective of porpoise occurrence. Complex interannual variation in foraging behavior was also shown across the time series. A strong nocturnal peak in foraging intensity was observed. We found increased porpoise foraging with dolphin species detections within the same hour, and a negative impact of construction activities, involving both impulsive and broadband noise. Results highlight the value of long‐term acoustic time series, by quantifying variation, and show that extracting foraging behavior from occurrence data can help to unravel habitat use patterns, responses to disturbance, and seasonal changes in behavior. Understanding when and how a species uses an area can better inform marine spatial planning and help mitigate anthropogenic impacts.